LOOKING FOR A WAY TO RESOLVE THE LEGAL STATUS OF THE CASPIAN SEA: INTERNATIONAL LAW PROVIDES NO ANSWER - KONDAUROVA, Viktoria (CENTRAL ASIA AND THE CAUCASUS, 2008)
As early as the 18th-19th centuries, the political disagreements among Great Britain, Russia, and Turkey over the Caspian Sea region brought about significant changes in its diplomatic reality. After World War I and II, the policy of the great powers also changed the diplomatic landscape of this region, which, despite all of the disputes, remained in the center of international attention. Control over the Caspian began to largely be viewed within the framework of the influence of the two main powers in the region: the Soviet Union and Persia. Later, when geological research determined the potential of the minerals on the seabed, particularly oil and natural gas, the world once more turned its attention to the region, this time for economic considerations. By the second half of the 20th century, globalization and the world market had become part and parcel of current reality, which meant that economic interests too had spread far beyond the framework of the national market. The sea’s status was settled between Iran and the Soviet Union: it was divided according to the principle of common usage or condominium (common property). But no mention was made of ownership, division, or use of the sea’s resources, thus the question of the Caspian’s legal status has become pertinent.The situation became even more aggravated at the beginning of the 1990s with the collapse of the Soviet Union and the formation of the new sovereign states in the region. The former Soviet republics, countries that are now independent of Moscow’s policy, along with Iran and the Soviet Union’s legal successor, Russia, began to declare their rights to the resources of the Caspian Sea, and its legal status became one of the most important and difficult-to-resolve international problems. It has been difficult to find a satisfactory answer for all the parties concerned to a question that affects national interests, the environmental aspects of the Caspian Basin, the interests of oil and gas companies, as well as the very sensitive security problems of the world powers